Literacy extension programs of higher education institution in the Philippines: insights from stakeholders - Martin, Matronillo Del Mundo; Cruz Ildefonso, Lhea dela (International Journal of Evaluation and Research in Education (IJERE), 2025)
This descriptive research investigates the impact of extension programs from a college of teacher education on public elementary school teachers. Three programs, literacy (n=75), Catch Me and Teach Me strategy literacy program (n=64), and campus journalism (n=48), were evaluated. Participants reported profound positive impact from these programs, considering them effective or very effective. The literacy program significantly improved reading and writing skills, fostered a love for learning, and benefitted the community. However, challenges like outdated materials and overemphasis on rote memorization need addressing. The Catch Me and Teach Me strategy literacy program excelled in practical teaching strategies and hands-on learning but required additional time and support, emphasizing the need for a more personalized approach. The campus journalism program was lauded for its informativeness but faced venue, food quality, time management issues, and a desire for more diverse topics. These findings stress the importance of customized professional development, long-term impact assessment, cultural sensitivity, and community involvement. Effective, engaging training methods, feedback, and efficient resource allocation are vital for program improvement. The research aims to enhance extension services’ quality for the community's benefit, providing valuable guidance to improve these programs and cater to participants' diverse needs.